In the Mind, the Household, or the Market? : Concepts and Measurement of Women's Economic Empowerment - Fox, Louise; Romero, Carolina (World Bank, Washington, DC, 2017)
The concept of empowerment is now widely used in several disciplines to characterize the states and social processes of individuals and communities. In economic development, the concept has come to mean women's power and agency in all economic domains and market-related interactions—earning, spending, and saving income; buying, owning, and selling assets; holding and inheriting wealth; starting and operating a business; acquiring a bank account or credit; and participating in or leading a union or other form of economic collective action. Measurement has lagged conceptualization. Most analytical research by economists, primarily involving impact evaluation, has measured empowerment as women's influence over household expenditures. This is a very narrow sliver of empowerment; not surprisingly, it is not well correlated with other economic or social outcomes. This paper suggests measuring empowerment in eight facets (a 4 x 2 matrix): (a) attitudes and (b) behaviors, in the domains of (i) transactions and markets; (ii) social interactions, including mobility and reproductive freedom; (iii) political and civic participation, including exercising legal rights; and (iv) psychology, including self-confidence and ability to seek mental health.